Issues and Challenges of Experienced Counselors to Obtain Counseling Services in Malaysia - Mohd. Shahrul bin Kamaruddin; Jamayah Saili; Chin Chew Lin (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2022)
Counseling services are usually provided by counselors to specific target groups such as students, parents, and the community. However, the aim of this study is to look at the challenges of counselors themselves to obtain counseling services. This study is a qualitative study in the form of semi-structured interviews among eight counselors with more than 10 years of experience. The scope of the study revolved around exploring the challenges of obtaining counseling services. Data were analyzed by using the thematic analysis method that has been recommended by Braun and Clark (2006). The findings of the study found that the challenge for counselors to obtain counseling services is perception and stigma, the counselor's personal attitude, and the counselor's way of thinking. Discussion and implications of the study are also discussed in this study.